MENANAM DENGAN METODE HIDROPONIK UNTUK MEMPERKUAT KETAHANAN PANGAN DI KELURAHAN SUKARAME - Iqbal, Muhamad; Kahar, Kahar; Kamaludin, Ade (Poltekkes Kemenkes Bandung, 2024)
Food security ensures everyone has sufficient, safe, nutritious, affordable access to healthy food. To achieve this, four critical dimensions must be met: accessibility, availability, safety and nutritional quality of food. Food security will be disrupted if one of these dimensions is not achieved. Hydroponics, which allows cultivating plants without soil, is an alternative for increasing food security, especially in areas with limited land. In Bandung, with a tropical climate and sufficient water availability, hydroponics can improve agricultural production efficiency and reduce pesticide use. Bandung Ministry of Health Polytechnic, Department of Environmental Health, carries out community service in the Sukarame area to overcome the limited knowledge and skills of the community regarding the use of home gardens, the importance of healthy pesticide-free vegetables, and the application of hydroponics. This program uses a scientific approach with lecture, discussion and field practice methods. The activity began with a survey, followed by briefing students participating in the service regarding hydroponics. Students are then involved in training and field practice. Measurement of residents' knowledge showed a significant increase from pre-test to post-test. Even though 20% of respondents still did not understand the material, these results show that practice-based training effectively increases knowledge. To ensure sustainability, continued assistance and provision of adequate resources is needed.